Optimalisasi Objek dan Sasaran Supervisi Pendidikan Sebagai Upaya Peningkatan Mutu - Khairunnafi; Muhib Mardhaqus; Ali Nurhadi; Tobi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Improving the quality of education is a strategic challenge that requires a systematic and sustainable approach. Educational supervision plays a central role in this effort, functioning as a mechanism for monitoring, guiding, and developing educational practices, both academic and managerial. This study employs a qualitative approach with a literature review to analyze the conceptual framework of supervision as an instrument for improving educational quality. The analysis emphasizes the integration between the objects of supervision—which include the planning, implementation, and evaluation of learning, school program management, and the professional development of teachers and educational staff—and the targets of supervision, which encompass teachers, principals, educational staff, and the organizational system of educational institutions. The findings indicate that the effectiveness of supervision is influenced by the competence of supervisors, teachers' understanding, infrastructure support, and strategies such as transforming the role of supervision into creative functional supervision, coaching, reflective practice, structured academic supervision, continuous professional development, and contextual collaborative approaches. Integrated supervision serves as a bridge between normative standards and educational practices, strengthens a culture of professional learning, closes the gap between planning and implementation, and promotes the continuous improvement of educational quality. The results of this study provide a conceptual contribution to the development of educational supervision and strategic recommendations for the implementation of more effective supervisory practices in schools